A new love for Charlotte - Lillard, Amy (Lillard, Amy. Wells Landing series, 2021)
"With her daughter newly married, widow Charlotte Burkhart should have been content to find a companion for her later years in Amish widower Glenn Esh. Yet, Charlotte longs for more than life has offered her thus far. When she discovers a baby on her doorstep, the child seems like the miracle Charlotte's been praying for. Unfortunately, Glenn doesn't feel the same way." -- provided by publisher.